TEKNIK PENILAIAN SIKAP, PENGETAHUAN DAN KETERAMPILAN - Andita Dwi Puspita Ningsih; Ulfa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
ssessment of attitudes, knowledge, and skills is an essential component of the learning process, providing a comprehensive overview of students’ development. This study employs a literature review method by examining various sources related to assessment techniques in the affective, cognitive, and psychomotor domains. The findings indicate that attitude assessment can be conducted through observation, self-assessment, and peer assessment to evaluate students’ spiritual and social behavior. Knowledge assessment is carried out through oral tests, written tests, and assignments to measure students’ understanding and cognitive abilities. Meanwhile, skills assessment focuses on students’ ability to apply knowledge using performance assessment, project assessment, and portfolio techniques. Overall, the application of appropriate and authentic assessment techniques enhances the quality of learning and supports teachers in providing effective follow-up tailored to students’ needs